HIJAB BAGI WANITA MUSLIMAH DI ERA MODERN - Sofiyah, Ahla; Zafi, Ashif Az (Universitas Islam Negeri Raden Intan Lampung, 2020)
In modern times, clothing is not only used as self-protection, but also has its own trends. In Islam clothing that is used has its own rules between men and women, namely for men from the navel to the knees, while for women that is all limbs except the face and palms, but many scholars have different opinions on these limits. Clothing used by these women, in Islam, known as the hijab. Hijab is one type of clothing that is synonymous with women. By using the hijab, such women can not be free to move, therefore hijab women become discriminated in certain areas. But hijab women are now the object of archery for the insurance industry because of the rise of hijabers that increasingly exist both in the real world and in the virtual world with the help of social media that is booming. Then came the sharing of businesses in the field of wisdom. That must be remembered in this hijab fashion in accordance with Islamic religious rules. The method used by the author in making scientific works is to use field research methods, by looking at overall what is happening in the community.